Prototype of Early Warning System for Home Door Security Based on IoT Using Piezoelectric Sensor - Abdul Hafizh; Nur Kholis; M Syariffuddien Zuhrie; Arif Widodo (INAJEEE (Indonesian Journal of Electrical and Electronics Engineering), 2020)
Early warning system of door security based on IoT with piezoelectric sensor, this was an early warning system wich could detect a threat on the door and send a notification to the owner smart phone to do preverentive action. This system was made with affordable cost, wich anyone can own this not only the rich one. This system will classified wich a safe knkck and a threat. This system used piezoelectric sensor to monitor a threat and buzzer to make some noise around. This system was equiped a relay to control the solenoid lock as your primary lock. This system used blynk cloud as the based wich could be operated on smart phone. The test used one room and one door. Take a survey to decide wich a normal knock and a stroke. And as got the result, then set the set point based on the output voltage of the sensor, as a threat to the door. Wich that the microcontroller could send a notification to the blynk apps on smart phone. After tahat we did some test to the respond time of, notification, buzzer, and the relay. Wich the respond time of notification was 2,15 second, the buzzer was 1,1 second, and the relay was 1,15 second. This system has 80% accuracy. This system might be well monitored the door with blynk apps.